No turning back : a memoir - Fulton, Edward Thomas Whyte, 1904-1999 (Sullivan's Creek series., 2005)
The shifting scenery of Ted Fulton's life--from Sydney to Hong Kong, Singapore, the Middle East and Melbourne--is played out against the anchoring backdrop of Papua New Guinea where he ventured as a young man. Containing a unique account of life behind enemy lines in the jungle of New Guinea and of Australia's World War II engagement in the Pacific, this laconic memoir roves across the decades. Spanning a lifetime of joys and sorrows, No Turning Back records the achievements of a man whose thirst for adventure drove him to find fulfilment and a sense of identity in locations far from home. Arriving in Papua New Guinea in his early 20s and spending the next 40 years as gold miner, soldier and planter, Ted Fulton built a life that developed as the nation grew. A powerful reminder that Australia's relationship with Papua New Guinea is founded on more than the notorious combination of politics, power and wealth, Ted writes of his home with moving insight and appreciation of the rugged beauty of the land and its people.--Publisher's note.